Küche des Hauses in Osogbo (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Artists; Interior decoration; Mosaics; Photographs; Osogbo; Nigeria; Art Collector; Art Collecting